Analisis Lngkungan kerja Pengaruh Lingkungan Kerja, Kompetensi dan Motivasi Terhadap Kinerja Perawat RSM Siti Khodijah Gurah Kediri di Era Pandemi - Fina Fitriani; Arisyahidin Arisyahidin; Mohammad Naim Musyafik (Otonomi, 2022)
This study aims to determine whether there is a positive influence simultaneously or partially between work environment, competence and motivation with nurse performance. The method used is descriptive quantitative, multiple regression analysis tools and data collection techniques in the form of questionnaires and interviews. Respondents used 60 employees with saturated samples. The results of this study are (1) Simultaneously work environment, competence and motivation have a positive effect on nurse performance. (2) Partially, the work environment has a positive effect on the performance of nurses. (3) Partially, competence has no effect on nurse performance. (4) Partially, motivation has no effect on nurse performance. Suggestions for improvement that can be done are by sufficient and facilitating the qualification requirements for training not only participating in training between hospital networks but further expanding the training area and providing easy learning tasks for trainees regardless of their employment status. The second is for work motivation to recalculate the proportion of togetherness without reducing the workload and the risk of the emergency level, in addition to services which are shared on the principle of togetherness, it is proposed to hold a work culture competition with the aim of not only motivating nurses to work but also improving the quality of hospital services